Proceedings of International Conference of Aerospace and Mechanical Engineering 2019 : AeroMech 2019, 20–21 November 2019, Universiti Sains Malaysia, Malaysia /: AeroMech 2019, 20–21 November 2019, Universiti Sains Malaysia, Malaysia. (2020) - Unknown
No abstract available